2x+(6x-7)=(103-x)

Simple and best practice solution for 2x+(6x-7)=(103-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+(6x-7)=(103-x) equation:



2x+(6x-7)=(103-x)
We move all terms to the left:
2x+(6x-7)-((103-x))=0
We add all the numbers together, and all the variables
2x+(6x-7)-((-1x+103))=0
We get rid of parentheses
2x+6x-((-1x+103))-7=0
We calculate terms in parentheses: -((-1x+103)), so:
(-1x+103)
We get rid of parentheses
-1x+103
Back to the equation:
-(-1x+103)
We add all the numbers together, and all the variables
8x-(-1x+103)-7=0
We get rid of parentheses
8x+1x-103-7=0
We add all the numbers together, and all the variables
9x-110=0
We move all terms containing x to the left, all other terms to the right
9x=110
x=110/9
x=12+2/9

See similar equations:

| 33=99-x | | 2(1/2x-6)=11 | | (x)=3x^2+1 | | 100=12x+13Y | | F(-5)=x^2-2x+7 | | (9x+16)(19x+3)(6x+15)=180 | | 3r=-42 | | 12.50+5/9=x | | 12=15n=33 | | 1x+1.2x-5.4=−10 | | 2({1}{2}x-6)=11 | | -28=x+4 | | 3(x-5)^2=363 | | 2/3x-8=x-17 | | 27=12x+6x+1+2 | | (2x+3)=(9x-25) | | 12(f+5)=138 | | 3(x–5)=2x–3 | | 4g-36=-12 | | 27=12x+1+2 | | -18=-9c | | 3+5x=(4x+7)=4(7x+3)-3 | | 9x44+6x+3=77 | | 1.2*8.5=1.7x | | -3x+4=5x+7 | | 2*x1x=49 | | -4.5+4.5=+y3 | | n=17.53-n | | 11+1x+22=67x+33 | | x/10=3.5/4 | | 4(x+2)=-(x-33) | | 10.5n=63 |

Equations solver categories